ICT On Education Management In Digital Age - Ni Wayan Ramini Santika (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
The rapid growth of digital media requires the contribution of education management to build future genagetions in utilizing information. This digital age is indispensable the use of digital or internet-based communication and information devices. Media intelligence and digital litagecy skills are the strategies to encourage media intelligence, including being creative, producing content, and utilizing it effectively. Education is a place to transform science and technology for the benefit of human life. Education management is required to anticipate global changes accompanied by advances in science and information technology. Education management is implemented so that education is easier to develop in this digital age. And the objective is that the implementation of a planned business is systematically planned and can correctly, accurately, and complete evaluated so that it achieves its goals in a productive, quality, effective and efficient manner. The education management in digital age functions can be studied from the main activities carried out by managers, through planning, implementation, and assessment. The management process genagelly follows the steps of planning, organizing, leading, and controlling. The benefits of ICT, Information and Communication Technology utilized Learning Multimedia Programs and Web-based Learning. And it's proposed ICT as support system of Education Management in the Digital Age.